2021
DOI: 10.1002/solr.202100162
|View full text |Cite
|
Sign up to set email alerts
|

Bifacial Color‐Tunable Transparent Photovoltaics for Application as Building‐Integrated Photovoltaics

Abstract: Transparent photovoltaics (TPVs) have attracted enormous attention due to their potential to be applied as building‐integrated photovoltaics (BIPV). Transparent and semitransparent photovoltaics have achieved a high level of efficiency, but there are still a number of issues that limit their application, such as their device size, lack of stability, and transmittance in the visible wavelength region. The excellent color implementation of a bifacial color‐tunable (BCT) TPV by tuning the indium tin oxide (ITO) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…As presented in Figure c, the gradient energy band dictates the extension of the space-charge region with the graded energy potential, resulting in the smooth movement of carriers. A TPV with an embedded Si thin film has been demonstrated (100 cm 2 ), which is close to the practical use of TPVs on-site and offers fine-tuning of TPV colors …”
mentioning
confidence: 55%
See 2 more Smart Citations
“…As presented in Figure c, the gradient energy band dictates the extension of the space-charge region with the graded energy potential, resulting in the smooth movement of carriers. A TPV with an embedded Si thin film has been demonstrated (100 cm 2 ), which is close to the practical use of TPVs on-site and offers fine-tuning of TPV colors …”
mentioning
confidence: 55%
“…The continuous and rapid exchange of information between the sensors and the neurons allows humans to perform multiple functions simultaneously. The number of neurons and synapses in the adult brain is estimated to be around 10 10 and 10 15 , respectively. ,, Spiking neurons, the primitive element of biological neural networks, are also the primary signaling unit of the nervous system. The presence of ion channels (for instance, Ca 2+ or K + ; see Figure b) assists the spike transduction across the cell membrane, where the information is collected by the dendrite (input connection network) and travels further through the axon (output connection), which transports the electrical signals in neural circuits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the device generated an output power of 6 mW under UV light (𝜆 of ~365 nm and I of ~70 mW/cm 2 ). Kim et al [15,79,80] demonstrated an Si-embedded TPV with a device configuration of glass/FTO/AZO (10 nm)/ZnO (400 nm)/Si (15 nm)/NiO (80 nm), wherein the Si thin films were deposited using plasma-enhanced chemical vapor deposition (Fig. 6).…”
Section: Photovoltaic Performance Of Inorganic Tpvsmentioning
confidence: 99%
“…Recently, new published works have shown that by embedding ultrathin a-Si:H layers in oxide-based devices, it was possible to increase significantly the PCE while maintaining high AVT and CRI values. [9][10][11][12][13][14][15] In this work, transparent PV cells based on ultrathin intrinsic a-Si:H and oxide-based charge-transport layers (CTLs) are presented. The a-Si:H films have been studied in detail via optical characterization techniques including photothermal deflection spectroscopy (PDS) as well as UV-visible-near infrared (NIR) spectrophotometry.…”
Section: Introductionmentioning
confidence: 99%